Proceedings of the 2017 ACM Conference on Computer Supported Cooperative Work and Social Computing 2017
DOI: 10.1145/2998181.2998194
|View full text |Cite
|
Sign up to set email alerts
|

#Indigenous

Abstract: With fewer than 66% of eligible voters registered and voter turnout rates 5-14 percentage points lower than any other ethnic group, Native Americans comprise the least participatory ethnic group in U.S. political elections [42, 57, 49, 25]. While discourse surrounding Native American issues and interests has increasingly moved to social media [55, 56], there is a lack of data about Native American political discourse on these platforms. Given the heterogeneity of Native American peoples in the U.S., one way to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The role of social platforms like Facebook and Twitter in communicating, disseminating, and organizing movements is evident [51,55], especially for public advocates and organizations [32,52]. However, from organizers' perspectives, the ubiquity of these platforms introduces new problems in controlling action, decision-making and collective identity [6].…”
Section: Activism In the Digital Agementioning
confidence: 99%
“…The role of social platforms like Facebook and Twitter in communicating, disseminating, and organizing movements is evident [51,55], especially for public advocates and organizations [32,52]. However, from organizers' perspectives, the ubiquity of these platforms introduces new problems in controlling action, decision-making and collective identity [6].…”
Section: Activism In the Digital Agementioning
confidence: 99%
“…Although not directly studying NPOs, recent research on social media use has demonstrated its usefulness in revealing public opinions on social causes. Studies focused how other populations (including LGBT, racial equality activists, and Native American advocates) practice advocacy work through social media have been conducted [6,17,49]. There has also been ample work using social media data to understand, model, and predict people's opinions on political discourse (e.g., [24,46]).…”
Section: Related Workmentioning
confidence: 99%
“…These types of data analytics can be beneficial for understanding and potentially predicting social phenomena especially in situations of policy decisions or in the case of activism to further understand the influence and impact of social media activism. For example, researchers (Vigil-Hayes, Duarte, Deschine Parkhurst, & Belding, 2017) tracked the connective actions of Native American advocates on Twitter to gain an in-depth understanding of the ubiquitous and pressing political issues that can and should be addressed by political actors. Consequently, the quantification of data naturally leads to measuring impact, influence, or importance, which, in the case of studying digital activism, draws challenges since events, news, and trends can shift quickly.…”
Section: Decolonising Social Media Studies By Celebrating Survivalmentioning
confidence: 99%
“…Hashtag use in American Indian political discourse on Twitter have been categorised in one study as representing topics of identity, civil rights, current events, and environmental issues (Vigil-Hayes, Duarte, Deschine Parkhurst, & Belding, 2017). The use of hashtags in American Indian activist efforts not only can draw attention to specific causes but also can be used to support a greater movement of similar injustices across tribal groups, or even to connect to the global Indigenous community.…”
Section: Decolonising Social Media Studies By Celebrating Survivalmentioning
confidence: 99%